Trade Liberalization and Wage Inequality: New Insights from a Dynamic Trade Model with Heterogeneous Firms and Comparative Advantage - Wolfgang Lechthaler; Mariya Mileva (FIW - Research Centre International Economics, 2015)
We develop a dynamic general equilibrium trade model with comparative advantage, heterogeneous firms, heterogeneous workers and endogenous firm entry to study wage inequality during the adjustment after trade liberalization. We find that trade liberalization increases wage inequality both in the short run and in the long run. In the short run, inter-sectoral wage inequality is high but then recedes. The skill premium does not change much in the short run but increases substantially in the medium and long run. Incorporating worker training in the model considerably reduces the effects of trade liberalization on wage inequality. The effects on wage inequality are much more adverse when trade liberalization is unilateral instead of bilateral or restricted to specific sectors instead of including all sectors.
Keywords: E24; F11; F16; J31; J62; 330; trade libaralization; wage inequality; adjustment dynamics